Ventral Tegmental Area GABA Neurons Are Resistant to GABA(A) Receptor-Mediated Inhibition During Ethanol Withdrawal - Nelson, Ashley C.; Williams, Stephanie B.; Pistorius, Stephanie S.; Park, Hyun J.; Woodward, Taylor J.; Payne, Andrew J.; Obray, J. Daniel; Shin, Samuel I.; Mabey, Jennifer K.; Steffensen, Scott C. (Frontiers in Neuroscience, 2018)
The neural mechanisms underlying alcohol dependence are not well understood. GABAergic neurons in the ventral tegmental area (VTA) are a relevant target for ethanol. They are inhibited by ethanol at physiologically-relevant levels in vivo and display marked hyperexcitability during withdrawal. In the present study, we examined the effects of role of the GABA(A) receptor agonist muscimol on VTA GABA neurons ex vivo following withdrawal from acute and chronic ethanol exposure. We used standard cell-attached mode electrophysiology in the slice preparation to evaluate the effects of muscimol on VTA GABA neuron firing rate following exposure to acute and chronic ethanol in male CD-1 GAD-67 GFP mice. In the acute condition, the effect of muscimol on VTA neurons was evaluated 24 hrs and 7 days after a single in vivo dose of saline or ethanol. In the chronic condition, the effect of muscimol on VTA neurons was evaluated 24 hrs and 7 days after either 2 weeks of twice-daily IP ethanol or saline or following exposure to chronic intermittent ethanol (CIE) vapor or air for 3 weeks. VTA GABA neuron firing rate was more sensitive to muscimol than DA neuron firing rate. VTA GABA neurons, but not DA neurons, were resistant to the inhibitory effects of muscimol recorded 24 hours after a single ethanol injection or chronic ethanol exposure. Administration of the NMDA receptor antagonist MK-801 before ethanol injection restored the sensitivity of VTA GABA neurons to muscimol inhibition. Seven days after ethanol exposure, VTA GABA neuron firing rate was again susceptible to muscimol’s inhibitory effects in the acute condition, but the resistance persisted in the chronic condition. These findings suggest that VTA GABA neurons exclusively undergo a shift in GABA(A) receptor function following acute and chronic exposure. There appears to be transient GABA(A) receptor-mediated plasticity after a single exposure to ethanol that is mediated by NMDA glutamate receptors. In addition, the resistance to muscimol inhibition in VTA GABA neurons persists in the dependent condition, which may contribute to the the hyperexcitability of VTA GABA neurons and inhibition of VTA DA neurons during withdrawal as well as the motivation to seek alcohol.